An Unusual Salivary Gland Tumor Mimicking Papillary Thyroid Carcinoma: Mammary Analog Secretory Carcinoma - Asa, Sylvia L.; Mete, Ozgur (Frontiers in Endocrinology, 2018)
Thyroid tumors usually present as masses in the thyroid gland. While the majority of these tumors represent neoplasms of thyroid tissues, mainly of follicular epithelial cell differentiation, the differential diagnosis includes other lesions, such as C cell neoplasms (medullary thyroid carcinoma), intrathyroidal parathyroid or thymic tumors, soft tissue tumors and hematologic neoplasms as well as metastatic malignancies. Rare tumors are of salivary gland types. This case illustrates an unusual tumor of salivary gland type, an intrathyroidal mammary analog secretory carcinoma. The pathogenesis, diagnostic pitfalls and therapeutic implications of this unusual tumor are discussed.